A small-scale solar Organic Rankine Cycle power plant in Thailand: Three types of non-concentrating solar collectors. (1st March 2018) - Sonsaree, Sorawit; Asaoka, Tatsunori; Jiajitsawat, Somchai; Aguirre, Hernan; Tanaka, Kiyoshi
Highlights: Small-scale solar ORC power generation from low-temperature heat is proposed. Three types of non-concentrating solar collectors are compared. The economic analysis in terms of levelized cost of electricity is performed. The environment assessment in terms of CO2 emission is investigated. Abstract: Power generation from solar energy is one of many alternative ways to solve the current energy crisis and environmental problems affecting our world. In this study, a system that utilizes low-temperature heat (under 100 °C) from solar energy to generate electricity by a small-scale Organic Rankine Cycle system is proposed. The system is analyzed using three different capacities of the ORC system with R-245fa (20, 40 and 60 kWe ) in combination with solar water heating system (SWHS), using four different models (SORC-I, SORC-II, SORC-III, and SORC-IV). Compound parabolic concentrator (CPC), evacuated-tube and flat-plate collectors were used to generate heat with optical efficiency ( FR ( τα ) e ) of 0.72, 0.57, 0.74, overall heat transfer coefficient ( FR UL ) of 0.97, 0.75, 3.62 W/m 2 -K, and collector area of 2.16, 2.37, 2.08 m 2 per unit, respectively. The maximum power output, the CO2 emission, and the economic analysis in terms of levelized cost of electricity (LCOE) were evaluated by a mathematical model. The weather data from Bangkok, a representative city in the central part of Thailand, was used for simulations. The simulation results shown that, if the number of collectors is the same on all systems, the system can produce the highest power output when combined with the CPC collectors. In terms of the economic analysis, the 60 kWe ORC system has the lowest LCOE value of 0.20 USD/kWh if coupled with 950 units of evacuated-tube collectors without initial investment of the collectors into consideration. In this case, the system can produce the power output of 113.5 MWh/Year, and reduce CO2 emission of 62.2 Ton CO2 eq./Year. If investment cost is taken into account, a LCOE of 0.67 USD/kWh can be achieved by the same system but coupled with 900 units of the same collectors. In this case, the system power output is 110.0 MWh/Year, and CO2 emission are reduced by 60.3 Ton CO2 eq./Year.